Psychological burden and caregiver-reported non-adherence to psychotropic medications among patients with schizophrenia. (January 2018) - Kretchy, Irene A.; Osafo, Joseph; Agyemang, Samuel Agyei; Appiah, Bernard; Nonvignon, Justice
Abstract: The study examined the association between psychological distress, caregiving burden and caregiver-reported medication adherence in 444 informal family caregivers of patients with schizophrenia. Participants were assessed on the Depression, Anxiety Stress Scale, Zarit Burden Interview and the Medication Adherence Report Scale. Caregivers reported a non-adherence rate of 54.5% among patients with schizophrenia. Poor adherence to antipsychotics was significantly associated with caregiver burden (p < 0.01) and experience of anxiety (p < 0.0001). The burden of caregiving should be considered during the assessment of adherence. The findings suggest a need for culturally appropriate interventions that improve antipsychotic adherence of outpatients with schizophrenia with specific attention to the burden of the caregiver. Highlights: Ghanaian caregivers reported 54.5% non-adherence rate to psychotropic medications among outpatients with schizophrenia. Patients whose caregivers had high anxiety and stress were significantly more likely to be non-adherent, as reported by the caregiver. An increase in burden leads to an increase in the odds of non-adherence.